2014
DOI: 10.1016/j.ecoenv.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective metabolism, distribution, and bioaccumulation brof triadimefon and triadimenol in lizards

Abstract: a b s t r a c tIn this research, Chinese lizards (Eremias argus) were chosen as laboratory animal to evaluate the stereoselectivity in the processes of metabolism, distribution, and bioaccumulation of triadimefon. A validated chiral high-performance liquid chromatography coupled with triple quadruple mass spectrometry (HPLC-MS/MS) method was developed for determining enantiomers' residues of parent compound triadimefon and its metabolite triadimenol in lizard blood and tissues. Pharmacokinetic results of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…However, C max time in S-(+)-TF (6 h) was faster than that in R-(-)-TF (12 h). Similar results were found in Kenneke et al (2010) on rainbow trout and in Wang et al (2014). Until the end of the experiment (7 days), there was still slight triadimefon residue (Figs.…”
Section: Degradation Of Triadimefon In Tissues and Plasmasupporting
confidence: 86%
See 2 more Smart Citations
“…However, C max time in S-(+)-TF (6 h) was faster than that in R-(-)-TF (12 h). Similar results were found in Kenneke et al (2010) on rainbow trout and in Wang et al (2014). Until the end of the experiment (7 days), there was still slight triadimefon residue (Figs.…”
Section: Degradation Of Triadimefon In Tissues and Plasmasupporting
confidence: 86%
“…To ensure the deglutition of triadimefon by lizards, we pushed the lavage needle very slowly in order to give them enough time to assimilate the pharmaceutical, and kept their mouths closed for a few minutes after dosing. In the previous research, a preliminary experiment at 90 mg/kg bw was conducted which no difference clinical signs were found between the control and treated groups (Wang et al, 2014). So, in present study, the control group was only sacrificed at 168 h. The organs including liver, brain, kidney and fat in each group were weighted and collected in heparinized tubes separately.…”
Section: Degradation Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…2,3 These compounds inhibit fungal proliferation by inhibiting steroid demethylation. [11][12][13][14][15] Among these complexes, complexation of pesticides with Cu(II) has potential advantages including the enhancement of persistence, longer shelflife, reduction of mammalian toxicity and conversion of nonsystemic to systemic pesticides. [5][6][7] Recently, the complexes, containing transition metal and 1,2,4triazole ligands have been extensively investigated, mainly because of not only their innovative structures [8][9][10] but also their application values and development potential in optical, electrical, various biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Stereoselective behaviors of TF and TN have been reported in soil microorganisms and rainbow trout (Garrison et al, 2011;Kenneke et al, 2010;Li et al, 2011). In our previous study (Wang et al, 2014), we reported the stereoselective metabolism, distribution and bioaccumulation of TF and TN in lizards under racemic form of TF exposure. These results gave us a preliminary understanding of stereoselective behaviors of TF and TN.…”
Section: Introductionmentioning
confidence: 73%